2018
DOI: 10.25041/fiatjustisia.v12no2.939
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Dilemma of The Limitation of Granting Remission for Corruption Prisoners

Abstract: Corruption is an extraordinary crime, so the law enforcement for corruption cases must also be done extraordinarily. Therefore

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is because convicted terrorists are prisoners who are not said to have committed ordinary crimes, but crimes caused by radical ideology's deviation from societal norms. Thus, it requires special treatment slowly to break away from the ideology of their movement (Maroni & Ariani 2018). Although standard procedures have been regulated in the implementation of deradicalization of those convicted of terrorism, by reviewing findings with various motives and causes of terrorism, a unique rehabilitation concept for convicted terrorists is required (Zhou 2019).…”
Section: Using a Soft-line Approach To Realize Maqashid Al-shari'a Valuesmentioning
confidence: 99%
“…This is because convicted terrorists are prisoners who are not said to have committed ordinary crimes, but crimes caused by radical ideology's deviation from societal norms. Thus, it requires special treatment slowly to break away from the ideology of their movement (Maroni & Ariani 2018). Although standard procedures have been regulated in the implementation of deradicalization of those convicted of terrorism, by reviewing findings with various motives and causes of terrorism, a unique rehabilitation concept for convicted terrorists is required (Zhou 2019).…”
Section: Using a Soft-line Approach To Realize Maqashid Al-shari'a Valuesmentioning
confidence: 99%
“…The concept of a welfare law state is the result of the development of the polizeistaat law state concept and the national law state concept 9 . This understanding of the rule of law is contained in the 4th paragraph of the Preamble to the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945), that one of the objectives of the Indonesian State is to advance public welfare 10 .…”
Section: Guidance and Supervision Of The Implementation Of This Ministerialmentioning
confidence: 99%
“…The United Nations (U.N) has warned that about 30% of pesticides marketed in developing nations contain toxic substances which pose a serious threat to both human health and the environment [40]. Some studies conducted in Ghana revealed levels of organochlorine pesticides in water, sediments, food and vegetable [26,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Some farmers are of the view that the more or as often as they apply pesticides the greater the chances of higher yield and also destroying crop pest [44].…”
Section: Introductionmentioning
confidence: 99%